Bone mineral density in patients with Cushing’s syndrome - ŞEKER, AYSUN; YAVUZ, DİLEK (My University, 2024)
Objective: Cushing’s syndrome is caused by the excessive secretion of cortisol or the intake of exogenous cortisol. Morbidity caused by osteoporosis is a major complication that cannot be ignored. We conducted a study to evaluate bone density and fracture risk factors in patients with Cushing’s syndrome. Patients and Methods: This retrospective case-control study involved 176 patients diagnosed with Cushing’s syndrome [153 female and 34 male patients] and 84 controls [72 female and 12 male patients]. Patients admitted to the clinics within the last eight years were included in the analysis. We collected demographic, clinic laboratory data, and bone densitometry measurements from electronic patient files. The classification of patients into normal, osteopenia, or osteoporosis groups is determined by their Body Mineral Density measurements based on the World Health Organization criteria. Results: Among the patients, 135 were diagnosed with Cushing’s disease and 41 with adrenal adenomas. Patients with Cushing’ syndrome showed a higher incidence of osteopenia (11.4%) and osteoporosis (2.8%) when compared to the control group. No osteoporosis cases were found in the control group, while nine cases of osteopenia were detected. Osteopenia was significantly more common in adrenal adenoma patients than in those with pituitary Cushing’s disease. Osteopenia was present in 39.1% of adrenal Cushing’s patients, with only 8.7% (n = 2) having osteoporosis. Osteopenia was observed in 11 patients (23.4%) with pituitary Cushing’s disease, while only 4 patients (8.5%) had osteoporosis. Conclusions: Osteopenia is more prevalent in patients with adrenal Cushing’s syndrome.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; BMD; Bone; Cushing’s syndrome; Low bone density; Osteopenia; Osteoporosis